Evaluation of alkaline phosphatase as a biomarker in the healing progression following tooth extraction: ALP as biomarker in post extraction healing - Pandian, Senthoor (2022)
Objective: The progression of a healing socket following an extraction is usually analysed through clinicalexamination and radiographic investigation. Whilst soft tissue healing is usually maintained well, healingprogression of hard tissue is more challenging to predict and manage, with issues such as a dry socket or malunionof the underlying bone. Serum biomarkers for bone healing progression, such as alkaline phosphatase(ALP), could prove helpful as a diagnostic tool for early intervention. Material and Methods: Twenty healthy18-30-year-old individuals who were to extract lower impacted wisdom teeth were included. 2ml of blood wascollected before treatment, 48 hours after then following samples were collected 1 month, 2 months and 3 monthsafter the procedure. Intra-oral radiographs were taken at the end of the three months. Results: There was asignificant correlation elicited with the healing and ALP levels at 1,2 & 3 months’ time intervals (p<0.05), where17 patients who had a substantial increase in the levels of ALP also had satisfactory healing after three months.Three individuals who did not show any increase in ALP level did not have satisfactory healing. Conclusion:ALP is a useful supplementary biomarker for bone healing. KEYWORDSAlkaline phosphatase; Tooth extraction; Bone healing; Oral surgery.